TECHNOLOGIES OF PRODUCTION OF CAST FRACTION OF IRON-CARBON ALLOYS OF JSC «BELNIILIT» . - D. A. Volkov; A. P. Melnikov; A. D. Volkov; P. S. Gurchenko (Литьë и металлургия)
The technology of production of iron-carbon alloys grit of JSC «BeLNiiLiT» are studied.